2007
DOI: 10.1111/j.1444-2906.2007.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of wild Mekong giant catfish Pangasianodon gigas collected from Thailand and Cambodia

Abstract: The Mekong giant catfish Pangasianodon gigas is endemic to the Mekong River and is a critically endangered species. The genotypes of the microsatellite DNA (msDNA) and mitochondrial DNA (mtDNA) markers (right domain of the control region) were detected to evaluate the present status of genetic divergence of this species from the Mekong River in Thailand and Cambodia. The observed and expected heterozygosity values of Mekong giant catfish in Thailand and Cambodia were relatively low in comparison with those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…The Mekong Basin is the largest contemporary drainage in SE Asia and is also the most zoologically diverse (Zakaria-Ismail, 1994;Campbell, 2009;Valbo-Jørgensen, Coates & Hortle, 2009). The few phylogeographical studies undertaken so far for the Mekong have tended to focus on migratory taxa, or at least those with a high dispersal potential (Na-Nakorn et al, 2006;Ngamsiri et al, 2007;Hurwood, Adamson & Mather, 2008;Adamson et al, 2009a). The few phylogeographical studies undertaken so far for the Mekong have tended to focus on migratory taxa, or at least those with a high dispersal potential (Na-Nakorn et al, 2006;Ngamsiri et al, 2007;Hurwood, Adamson & Mather, 2008;Adamson et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The Mekong Basin is the largest contemporary drainage in SE Asia and is also the most zoologically diverse (Zakaria-Ismail, 1994;Campbell, 2009;Valbo-Jørgensen, Coates & Hortle, 2009). The few phylogeographical studies undertaken so far for the Mekong have tended to focus on migratory taxa, or at least those with a high dispersal potential (Na-Nakorn et al, 2006;Ngamsiri et al, 2007;Hurwood, Adamson & Mather, 2008;Adamson et al, 2009a). The few phylogeographical studies undertaken so far for the Mekong have tended to focus on migratory taxa, or at least those with a high dispersal potential (Na-Nakorn et al, 2006;Ngamsiri et al, 2007;Hurwood, Adamson & Mather, 2008;Adamson et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that species' patterns of population structure can be quite diverse and that system‐wide models can be overly simplistic. For example, giant catfish Pangasianodon gigas Chevey populations in the Mekong River basin are essentially homogeneous over 1000 km of stream distance (Na‐Nakorn et al , 2006; Ngamsiri et al , 2007), whereas the congeneric suchi catfish Pangasianodon hypophthalmus (Sauvage) with a similar distribution exists as at least three discrete, yet sympatric, stocks in Cambodia alone (So et al , 2006 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the total number of P. gigas present in the area is estimated to have decreased by approximately 90% over the past two decades (Hogan et al, 2004), suggesting that this catfish is at risk of extinction in the wild. In addition, the Mekong giant catfish genetically forms a single population in the Mekong River basin, and mitochondrial and microsatellite DNA analyses have revealed remarkably low genetic diversity in the wild population as well as in blood stocks (Na-Nakorn et al, 2006Ngamsiri et al, 2007;Sriphairoj et al, 2007). Due to these findings, this catfish is currently listed as a critically endangered species in both the Conservation on International Trade in Endangered Species (CITES) Appendix I and International Union for the Conservation of Natural Resources (IUCN) Red List.…”
Section: Introductionmentioning
confidence: 99%